HUBUNGAN PENEMPATAN PEGAWAI DENGAN KINERJA PEGAWAI DI KANTOR DINAS SOSIAL PROVINSI SUMATERA BARAT - Ayu Oktaria (Universitas Negeri Padang, 2013)
The purpose of this study was to know about the staffing and employee performance, and found a significant association between the two variables. The Population are 112 employees and samples 57 employees, who were taken using stratifield proportional random sampling technique. The research instrument used a questionnaire with Likert scale models have been tested for validity and reliability. Data were analyzed using product moment correlation. The results of this study are indicates quite appropriate staffing, employee performance is good, and there was a significant relationship between the staffing of the performance employee at the Social service office of West Sumatra Province. Kata Kunci : Penempatan pegawai, kinerja pegawai